2021
DOI: 10.1021/acs.est.1c01567
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Ozone Isopleth Construction and Diagnosis for the Ozone Control Strategy of Chinese Cities

Abstract: Ozone (O 3 ) isopleths describe the nonlinear responses of O 3 concentrations to changes in nitrogen oxides (NO X ) and volatile organic compounds (VOCs) and thus are pivotal to the determination of O 3 control requirements. In this study, we innovatively use the Community Multiscale Air Quality model with the high-order decoupled direct method (CMAQ-HDDM) to simulate O 3 pollution of China in 2017 and derive O 3 isopleths for individual cities. Our simulation covering the entire China Mainland suggests severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 74 publications
1
38
0
Order By: Relevance
“…50 This estimation was much higher than the 2019 GBD report: 0.31 (95% UI: 0.15–0.49) million, as had been highlighted in another recent study, 25 which should be attributed to the use of high HR value among all included studies. We had also found some other studies using one singular HR value for population risk estimations, 17, 74-77 but we would still encourage further relevant studies to consider multi-study pooled RRs, which could effectively reduce the potential biases from a single study. The adaptability of the pooled RRs could be verified from the coverage of exposure levels, as the 25 studies identified in our review had embraced a wide range of exposure concentrations (Supplementary Text S1) to encompass the global surface O 3 variability.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…50 This estimation was much higher than the 2019 GBD report: 0.31 (95% UI: 0.15–0.49) million, as had been highlighted in another recent study, 25 which should be attributed to the use of high HR value among all included studies. We had also found some other studies using one singular HR value for population risk estimations, 17, 74-77 but we would still encourage further relevant studies to consider multi-study pooled RRs, which could effectively reduce the potential biases from a single study. The adaptability of the pooled RRs could be verified from the coverage of exposure levels, as the 25 studies identified in our review had embraced a wide range of exposure concentrations (Supplementary Text S1) to encompass the global surface O 3 variability.…”
Section: Discussionmentioning
confidence: 98%
“…There were two major units used to quantify the surface O 3 concentrations, nmol mol -1 or parts per billion by volume mixing ratio (ppbV) more frequently used by atmospheric modelling researchers, 17, 18, 25 and milligram per cubic metre by mass concentration (µg/m 3 ) widely used by public health studies. 12 These two units are interchangeable to each other based on the ideal gas law PV n RT , if the air temperatures (T) and pressures (P) are given, as presented in eqs 1–4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that the ozone chemical regime in most industrial cities in China is more likely to be VOC-limited while the rural area is in a NO x -limited or transition regime [13]. Studies also suggested that the formation regime in most areas in Sichuan Province except for Chengdu is NO x -limited [31]. In Chengdu, the ozone formation regime is categorized as VOC-limited for most of the time [32,33].…”
Section: Introductionmentioning
confidence: 99%